2014
DOI: 10.1007/s00216-014-8109-9
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS, LC-MSn, LC-high resolution-MSn, and NMR studies on the metabolism and toxicological detection of mesembrine and mesembrenone, the main alkaloids of the legal high “Kanna” isolated from Sceletium tortuosum

Abstract: Mesembrine and mesembrenone are the main alkaloids of Sceletium tortuosum, a plant species that was used for sedation and analgesia by the KhoiSan, previously known as Hottentots, a tribe in South Africa. After fermentation, the obtained preparation called "Kanna" or "Kougoed" was used by chewing, smoking, or sniffing. Today, Kanna gains popularity by drug users as legal high. For monitoring such consumption, metabolism studies are mandatory because the metabolites are mostly the analytical targets, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Kanna, however, is detected in forensics to be a component of ‘designer drugs’ or as adulterated (fake) marijuana, which confirms the psychotropic potential of S. tortuosum [92,93] …”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 73%
“…Kanna, however, is detected in forensics to be a component of ‘designer drugs’ or as adulterated (fake) marijuana, which confirms the psychotropic potential of S. tortuosum [92,93] …”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 73%
“…This data suggests that these alkaloids have very low oral bioavailability. A recent study has shown that mesembrine and mesembrenone are metabolically unstable in human liver microsomes (Meyer et al ., ). Additional factors such as instability in gastric and intestinal fluids may further contribute to observed low bioavailability of mesembrine and mesembrenone observed in this study.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, the main alpha‐cleaved fragment ion in the TPs with a carbon‐bonded hydroxylation in the pyrrolidine ring ( Ib , IIIb , Vb ), carried the oxygen, which indicated a bond with a higher stability in the collision cell. All detected N‐ oxides eluted after the unchanged compound (Table ), whereas carbon‐bonded hydroxylation usually elutes before the unchanged compound using reversed phase chromatography . So far, metabolism studies of MPHP, MPBP, and MOPPP have only been analyzed using GC–MS, where N‐ oxides are not observed.…”
Section: Resultsmentioning
confidence: 99%
“…All detected N-oxides eluted after the unchanged compound (Table 2), whereas carbon-bonded hydroxylation usually elutes before the unchanged compound using reversed phase chromatography. [11,[32][33][34] So far, metabolism studies of MPHP, MPBP, and MOPPP have only been analyzed using GC-MS, where N-oxides are not observed. Evaluation on microbial biotransformation of environmentally relevant compounds, including pharmaceuticals, using activated sludge models have reported N-oxide formation of tertiary nitrogens.…”
Section: N-oxide-tpmentioning
confidence: 99%